Analysis of The Conceptual Understanding of Elementary School Students on The Concept of Fractions through Distance Teaching Materials using WhatsApp Group - Hartono, Hartono; Sujana, Atep; Sopandi, Wahyu (International Conference on Elementary Education, 2021)
Learning carried out from a distance hurts students in remote areas, especially in Panguragan, Cirebon District. This study aims to 1) analyzing conceptual understanding through interviews, and 2) analyzing conceptual understanding through test results. The research location is one of the elementary schools in Panguragan, Cirebon District. The subjects in this study were students in grade 5 with a total of 24 students. Data collection techniques used in this study were through interviews and test results. The results of data collection were analyzed using descriptive quantitative data analysis techniques. From the results of interviews and test results, it was found that the student's conceptual understanding was still low. The average score obtained on conceptual understanding is only 28.50%. These results indicate that grade 5 students have a low mathematics conceptual understanding ability on fractions concept. This shows the need to improve the quality of learning through more creative and innovative distance teaching materials to improve student's conceptual understanding.